Does size matter? Authorship attribution, small samples, big problem. (14th November 2013) - Eder, Maciej
Abstract: The aim of this study is to find such a minimal size of text samples for authorship attribution that would provide stable results independent of random noise. A few controlled tests for different sample lengths, languages, and genres are discussed and compared. Depending on the corpus used, the minimal sample length varied from 2, 500 words (Latin prose) to 5, 000 or so words (in most cases, including English, German, Polish, and Hungarian novels). Another observation is connected with the method of sampling: contrary to common sense, randomly excerpted 'bags of words' turned out to be much more effective than the classical solution, i.e. using original sequences of words ('passages') of desired size. Although the tests have been performed using the Delta method (Burrows, J.F . (2002). 'Delta': a measure of stylistic difference and a guide to likely authorship. Literary and Linguistic Computing, 17 (3): 267–87) applied to the most frequent words, some additional experiments have been conducted for support vector machines and k -NN applied to most frequent words, character 3-grams, character 4-grams, and parts-of-speech-tag 3-grams. Despite significant differences in overall attributive success rate between particular methods and/or style markers, the minimal amount of textual data needed for reliable authorship attribution turned out to be method-independent.